A LITERATURE STUDY OF THE IMPORTANCE OF SELF-AWARENESS - Lio, Stefanus; Degeng, I Nyoman Sudana; Hambali, IM; Radjah, Carolina Ligya (International Journal of Psychosocial Rehabilitation, 2020)
Self-awareness is a core capability of human life that enables individuals to understand their emotions, strengths, weaknesses, needs, motives, values and goals of life. This paper surveys the self-awareness literature by focusing on the importance of self-awareness. In general, it is found that there are two aspects of life in which self-awareness shows its importance. First aspect is in personal life and the second is in social life. Personally, self-awareness allows individuals to make wise and responsible choices, be anticipative in preventing unhealthy and destructive behavior for themselves and others, opening space for constructive communication while eliminating egoism, and ultimately bringing happiness and welfare to the individual's life. While socially, self- awareness impacts on four areas of life namely education, counseling, leadership and social work. Therefore, the development of self-awareness should be done in every phase of life for self-awareness is an unending process that requires time, energy, and commitment.